Publications and Manuscripts - International Human Rights Law Institute
Contains publications, manuscripts, lectures, pre-prints and copied books related to the conflict in the former Yugoslavia. The items cover historical, ideological, legal, humanitarian, medical and gender aspects of the conflict. Some reference books are included. The material was used as support for the Commission's investigation.